2009
DOI: 10.1158/1078-0432.ccr-08-1287
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Magnetic Resonance Imaging for Predicting and Detecting Early Response to Chemoradiation Therapy of Squamous Cell Carcinomas of the Head and Neck

Abstract: Purpose: The aim of this study was to investigate the utility of apparent diffusion coefficient (ADC) for prediction and early detection of treatment response in head and neck squamous cell carcinomas (HNSCC). Experimental Design: Diffusion-weighted magnetic resonance imaging studies were performed on 40 patients with newly diagnosed HNSCC before, during, and after the end of chemoradiation therapy. Analysis was done on data from 33 patients after exclusion of 7 patients that had incomplete data. Results: Pret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
311
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(342 citation statements)
references
References 35 publications
22
311
4
Order By: Relevance
“…Our findings regarding the D and f values are consistent with previous studies 18, 19. Kim et al found that the median nodal tumor volume of the PR group was higher, but not significantly different from that of the CR group 11. In addition, the median volumes decreased significantly in the CR group at weeks 1 and post‐TX compared with the volumes at pre‐TX 11.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings regarding the D and f values are consistent with previous studies 18, 19. Kim et al found that the median nodal tumor volume of the PR group was higher, but not significantly different from that of the CR group 11. In addition, the median volumes decreased significantly in the CR group at weeks 1 and post‐TX compared with the volumes at pre‐TX 11.…”
Section: Discussionsupporting
confidence: 92%
“…Also, King et al13 reported a significant correlation between local failure and post‐TX ADC, but not pre‐ or intra‐TX ADC values. Kim et al11 reported a significant increase in ADC values observed in the CR group within 1 week of treatment in HNSCC. Our results also showed an increase in ADC values in the CR group at the intra‐TX week 3 compared with the non‐CR group.…”
Section: Discussionmentioning
confidence: 95%
“…The biologic basis for this finding remains unclear, but it can be speculated that a higher ADC is observed in necrotic tissue and in tissue with loss of cell membrane integrity, which may correspond to a more aggressive phenotype. It has also been reported that responding lesions show a significantly higher increase in ADC early after initiation of therapy than do nonresponding lesions (19)(20)(21)(22); this finding can be attributed to changes in cell density, resulting from cytotoxic therapy-induced necrosis or apoptotic processes. More studies with larger sample sizes are required to establish the utility of this technique in predicting overall survival or long-term disease-free survival.…”
Section: Clinical Applications and Limitations Of Dwi General Diagnosmentioning
confidence: 91%
“…Pretherapy ADCs in responding lesions have been reported to be significantly lower than those of nonresponding lesions in several cancers (20)(21)(22). The biologic basis for this finding remains unclear, but it can be speculated that a higher ADC is observed in necrotic tissue and in tissue with loss of cell membrane integrity, which may correspond to a more aggressive phenotype.…”
Section: Clinical Applications and Limitations Of Dwi General Diagnosmentioning
confidence: 99%
See 1 more Smart Citation